(3RHO GdCOdI aj eYQaI Gddgs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3HGH Gdbhd ai GdJhMjO s
(3BNQgG (B:s
(3bdJ dELeGY GdCeI hGdYJQI Ydjge GdSdGe Ydi KHhJge dge hGLHI ajge dGai ef ShGge hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds